2020
DOI: 10.1109/access.2020.2994415
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Evaluation of Deep Learning-Based Techniques for Traffic Prediction

Abstract: Deep learning-based techniques are the state of the art in road traffic prediction or forecasting. Several deep neural networks have been proposed to predict the traffic but they have not been evaluated under common datasets. Current studies analyze their capacity to predict road traffic in general but do not focus on their capacity to predict the formation of congestions. This is critical for avoiding congestions or mitigate their negative impact. This paper progresses the current state of the art by presenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 52 publications
(117 reference statements)
0
13
0
4
Order By: Relevance
“…The architecture of the eRCNN is depicted in Figure 3. We demonstrated in [31] that this architecture and the design of the eRCNN is the optimum one for predicting the traffic under normal traffic conditions and under traffic congestion. All the eRCNNs used in this work are trained using the backpropagation through time algorithm (BPTT) and the ADAM algorithm [33], which is a v Q ρ…”
Section: Traffic Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…The architecture of the eRCNN is depicted in Figure 3. We demonstrated in [31] that this architecture and the design of the eRCNN is the optimum one for predicting the traffic under normal traffic conditions and under traffic congestion. All the eRCNNs used in this work are trained using the backpropagation through time algorithm (BPTT) and the ADAM algorithm [33], which is a v Q ρ…”
Section: Traffic Predictionmentioning
confidence: 99%
“…In this study, we predict the traffic variables using an error recurrent convolutional neural network (eRCNN) [18], since we previously demonstrated that this network achieves the best traffic predictions using data from fixed traffic detectors under general traffic conditions and under traffic congestion [31]. The eRCNN model takes as input the estimates of the three fundamental traffic variables.…”
Section: Traffic Predictionmentioning
confidence: 99%
“…Due to traffic congestion, the most influential cities in China suffer economic losses of $1 billion every year [3]. The European Commission calculates that the annual cost related to traffic congestion is about 100 billion euros (1% of GDP) [4]. The traffic congestion raises gas consumption, aggravates environmental pollution, and raises residents' travel time [5].…”
Section: Introductionmentioning
confidence: 99%
“…Scholars improved the SVM algorithm and obtained its improved model, such as support vector regression (SVR) [22], least-squares support vector machine (LSSVM) [23,24], and least-squares support vector regression (LSSVR) [25]. In recent years, inspired by neural networks, new technologies such as deep neural networks and deep learning have been developing rapidly, and traffic flow prediction technologies are also constantly updated and improved [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The purpose is to capture the target, that is, to complete the GWO. According to Equation(28), the decrease in the value of→ a will cause the value of → A to fluctuate accordingly and → A ∈ [−1, 1].…”
mentioning
confidence: 99%